Investigation of Snow Compaction Methods and Equipment Conducted for Engineer Research and Development Laboratories, Fiscal Year 1949. Report of Investigations. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MA (1949)
Field tests were performed with both full scale and scale model equipment. Full scale tests were performed to measure effectiveness of various types of compaction and steam injection apparatus and to examine the effect of repeated breaking up and recompaction of the snow. Scale model pontons were used to investigate effects of individual variables on compaction results. Additional studies were performed covering static laboratory compaction, California Bearing Ratio, modulus of elasticity and photomicrography. This report describes tests conducted and presents in detail the results obtained, together with conclusions based on the results, and recommendations concerning future investigations. See also Appendix dated Jun 49, AD-495 993.